Esiodo e la proposta platonica di rinuncia alla ricchezza - Lo Casto, Claudia (Lexis, 2025)
The paper aims to examine some aspects of the reception of the Hesiodic myth in Platonic thought, in order to demonstrate, through an attentive analysis of some passages from the Republic, the Politic and the Laws, how Plato uses and reshaped the Hesiodic myth for pedagogical and political purposes. Within this context, Plato’s precise intention appears to be the creation of a truly sociological theory based on the deny of material goods and wealth, which is proved to be the basis for the preservation of the social stability in the καλλίπολις.